Características de los grupos colombianos de investigación categoría A1 en ciencias sociales (2014-2015) (2015)
A total of 3970 Research, Technological Development or Innovation Groups were recognized by Colciencias in the last Call for Measurement (Number 693 of the year 2014). This editorial presents the indicators that characterize the 36 Research Groups in Social Sciences that were classified in category A1 according to the results of this call, in order to contribute to the debate that has been generated around the crisis experienced by the social sciences with the current STEM education policies that are being implemented in Colombia and in different countries. Hence, at this time it is pertinent to ask the question: How to make Social Sciences a national priority?